MANAJEMEN PEMBELAJARAN METODE AT TANZIL DI TPQ ASRAMA KHUSUS ANAK USIA DINI - Rosi, Fathor; Kholidah, Maya (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2025)
This research is motivated by the phenomenon seen in the TPQ institution of special boarding school for early childhood Pesantren Sumber Bunga, namely being able to read the Qur'an well and correctly using the At Tanzil method. The purpose of this study is to describe: first, how to plan learning to read the Qur'an by applying the At Tanzil method in the TPQ Special Boarding School for Early Childhood Pesantren Sumber Bunga. Second, how is the implementation of learning using the At Tanzil method in the TPQ Special Boarding School for Early Childhood Pesantren Sumber Bunga. Third, what are the impacts of learning the At Tanzil method in the TPQ Special Boarding School for Early Childhood Pesantren Sumber Bunga. Fourth, what are the supporting and inhibiting factors in the implementation of learning management of the At Tanzil method in the special boarding school for early childhood Pesantren Sumber Bunga. This study uses a descriptive qualitative approach. Data collection techniques are carried out through observation, in-depth interviews, and field observations. This research was carried out from the time the research date was determined until it was completed. The results of the study indicate that: first, learning to read the Qur'an using the At Tanzil method at the TPQ Asrama Khusus Anak Usia Dini Pesantren Sumber Bunga was carried out optimally, starting from the preparation of teachers in preparing teaching materials, materials, methods, and media used in delivering the At Tanzil method.